Combined Basal and Foliar NPK Fertilization Effects on Soil Properties and Rice Production - Shiamita Kusuma Dewi; Winih Sekaringtyas Ramadhani; Naiya Aninda; Hery Novpriansyah; Afandi (Acta Solum, 2026)
Rice (Oryza sativa L.) productivity in intensively cultivated paddy systems is limited by soil fertility loss and low nutrient use efficiency of conventional NPK fertilization, which is prone to ammonia volatilization, leaching, and phosphorus fixation in tropical soils. Foliar NPK application is proposed to bypass soil nutrient losses and improve fertilizer efficiency, but its combined effects with basal fertilizer on soil properties and rice production in tropical paddy conditions are poorly understood. This study aimed to evaluate the effects of combined basal and foliar NPK fertilization on selected soil properties and rice production under tropical paddy conditions in Central Lampung. A field experiment was conducted using a Randomized Complete Block Design with 8 treatments and 4 replications, comprising combinations of basal and foliar NPK. Soil properties, including pH, soil dispersion ratio, and soil texture, alongside agronomic parameters, were associated with rice production. The results showed that combined basal and foliar NPK application significantly affected soil pH, with treatment H having a higher soil pH than the control and the standardized fertilizer. Combined application also significantly improved rice agronomic performance, with treatment H recording the highest rice production of 4.23 kg plot⁻¹, representing a 50% increase over the control treatment. These findings show that combining basal and foliar NPK fertilization can potentially manage nutrients to sustain soil fertility and enhance rice production in tropical paddy systems.